Changes in Hemostasis and Lipid Metabolism in Postmenopausal Women Receiving Hormone Replacement Therapy: Effects of Natural and Synthetic Progestogens - Li-Fen Teng; Fang-Ping Chen (Elsevier, 2004)
Objective: In this study, we evaluated hemostatic factors related to cardiovascular disease in postmenopausal women receiving estrogen or combined progestogen replacement therapy. We further compared the effects of natural and synthetic progestogens on lipid profiles and hemostatic factors. Materials and Methods: Of the 60 subjects, 20 who had undergone a hysterectomy used conjugated equine estrogen (CEE; 0.625 mg/day) alone (group I); the other 40 used CEE (0.625 mg/day for 21 days) plus either micronized progesterone (200 mg/day; group II; n = 20) or medroxyprogesterone acetate (10 mg/day; group III; n = 20) for the final 10 days. The effects on lipid profiles and hemostatic parameters were evaluated at baseline and after 6 and 12 months of treatment. Results: Only group I patients showed a significant reduction in low-density lipoprotein cholesterol (LDL-C) and the atherogenic ratios of total cholesterol/high-density lipoprotein cholesterol (HDL-C) and LDL-C/HDL-C, as well as an increase in triglycerides. Tissue plasminogen activator levels decreased significantly in group I but did not change in groups II or III. Antithrombin III and protein S levels decreased significantly in group I but increased in groups II and III. Group I patients showed a stronger increase in protein C than those in either group II or III. There were no significant differences in hemostatic parameters between groups II and III. Conclusion: Estrogen replacement therapy may have beneficial effects on lipid profile and fibrinolytic factors in postmenopausal women. Both natural and synthetic progestogens attenuated the effects of estrogen. The 1-year effects of hormone replacement therapy on factors related to venous thromboembolism were positive. Micronized progesterone was not superior to medroxyprogesterone acetate.